2021
DOI: 10.47626/1679-4435-2021-615
|View full text |Cite
|
Sign up to set email alerts
|

Work activity and musculoskeletal symptoms in female cashiers

Abstract: Introduction Musculoskeletal symptoms affect several professional categories, including cashiers, who make repetitive movements. Irregular ergonomic aspects referring to poor postures cause physical and mental debilitation, leading to work-related musculoskeletal disorders. Objectives To correlate musculoskeletal disorders with an ergonomic analysis of the workstation used by cashiers. Methods A cross-sectional study was conducted for evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
1
1
1
Order By: Relevance
“…49 Additionally, the findings of the study indicated that the shoulders (51.5%), lower back (40.0%) and upper back (33.5%) were the most affected body regions. This finding was higher than that of a study report from Brazil, 7 which reported that 38.5%, 34.6%, and 30.8% of cashiers, respectively, complained of shoulder, lower back, and upper back pain. This variation could be caused by differences in the study period, sample size, sampling technique and the study population's knowledge about the variable of interest.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…49 Additionally, the findings of the study indicated that the shoulders (51.5%), lower back (40.0%) and upper back (33.5%) were the most affected body regions. This finding was higher than that of a study report from Brazil, 7 which reported that 38.5%, 34.6%, and 30.8% of cashiers, respectively, complained of shoulder, lower back, and upper back pain. This variation could be caused by differences in the study period, sample size, sampling technique and the study population's knowledge about the variable of interest.…”
Section: Discussioncontrasting
confidence: 75%
“…Cashiers are among the top 10 occupational working groups at risk of WRMSDs 6. A study from Brazil7 revealed that 38.5%, 34.6%, and 30.8% of cashiers experienced shoulder, lower back, and upper back pain, respectively. According to a study from Saudi Arabia,8 90% of supermarket cashiers had developed WRMSDs over a year, with the neck (66.84%) and lower back (65.80%) being the most affected body regions.…”
Section: Introductionmentioning
confidence: 99%
“…Para além do tratamento medicamentoso que deve ser prescrito pelo médico nos casos de dor intensa, a empresa deve investir em mobiliários e medidas ergonômicas e de segurança do trabalho para se prevenir o aparecimento das doenças ocupacionais. Assim, para amenizar ou até aliviar a pressão nos pés, nas costas e tornar a posição em pé mais confortável, pode-se fornecer uma almofada acolchoada ou um banco de elevação para elevar um pé de cada vez, permitindo que o operador de caixa mude de posição, alivie a pressão nas pernas e na região lombar (Roxô et al, 2021).…”
Section: Métodounclassified